Transformative of Problem-Based Learning Model to Enhance Learning Outcomes of Muhammadiyah High School Students - Nia Anggraeni; Irfan Kholid Sofhan (Ihsan Cahaya Pustaka, 2025)
This study examines the transformative application of the Problem-Based Learning (PBL) model to improve learning outcomes of Muhammadiyah high school students. The research responds to the demand for developing critical thinking, problem-solving skills, and conceptual understanding in line with the Muhammadiyah educational mission. Using a quasi-experimental design with a pretest–posttest control group, participants were drawn from selected Muhammadiyah high schools in Jember. Data were collected through achievement tests, classroom observations, and student reflections. Findings indicate that students taught with the transformative PBL approach achieved significantly higher learning outcomes than those in traditional instruction. This improvement was linked to active participation, collaborative group work, and contextual problem scenarios that connect lessons to real-life situations. The integration of transformative elements, such as character building, reflective practice, and digital learning support, further strengthened cognitive mastery and Islamic values. The study concludes that transformative PBL offers a viable instructional strategy to enhance both academic performance and character development, supporting Muhammadiyah's vision in the era of Society 5.0.